2014
DOI: 10.1136/jech-2013-203287
|View full text |Cite
|
Sign up to set email alerts
|

Does legislation to prevent alcohol sales to drunk individuals work? Measuring the propensity for night-time sales to drunks in a UK city

Abstract: BackgroundBy measuring alcohol retailers’ propensity to illegally sell alcohol to young people who appear highly intoxicated, we examine whether UK legislation is effective at preventing health harms resulting from drunk individuals continuing to access alcohol.Methods73 randomly selected pubs, bars and nightclubs in a city in North West England were subjected to an alcohol purchase test by pseudo-drunk actors. Observers recorded venue characteristics to identify poorly managed and problematic (PMP) bars.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 17 publications
4
28
1
Order By: Relevance
“…Our observation of a higher service rate later at night is consistent with previous observations [17,20,43], as was the increased likelihood of over-serving with greater intoxication level of other patrons [17,43,44] and with high music (or noise) level [18]. Consistent with Hughes et al [18], we found that over-serving was associated with a sum-score of indicators of problematic bars.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Our observation of a higher service rate later at night is consistent with previous observations [17,20,43], as was the increased likelihood of over-serving with greater intoxication level of other patrons [17,43,44] and with high music (or noise) level [18]. Consistent with Hughes et al [18], we found that over-serving was associated with a sum-score of indicators of problematic bars.…”
Section: Discussionsupporting
confidence: 82%
“…Most previous studies have used male actors [30] or they did not address gender differences or report the gender of the actors, whereas two studies found no significant association between patron gender and over-serving [45,46]. Similarly, an Australian study [47] found no statistically significant gender difference in survey respondents' reports of servers intervening when the respondents showed signs of intoxication at drinking establishments.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations